Cинтез та кристалічна структура двошарових індотитанатів Sr₂LnInTiO₇ - Тітов, Ю.О.; Білявина, Н.М.; Марків, В.Я.; Слободяник, М.С.; Полубінський, В.В. (Доповіді НАН України, 2014)
Визначено протяжнiсть областi сполук з шаруватою перовськiтоподiбною структурою (ШПС) в ряду двошарових перовськiтiв Sr₂LnInTiO₇. Синтезовано новi iндотитанати Sr₂LnInTiO₇ (Ln — La, Pr, Nd, Sm) при термообробцi еквiмолярних сумiшей
Sr₂TO₄ +LnInO₃ та визначено їх кристалiчну ШПС методом рентгенiвської дифракцiї
на порошках. Встановлено належнiсть ШПС Sr₂LnInTiO₇ (Ln — La, Pr, Nd, Sm) до
структурного типу BaLa₂In₂O₇ (пр. гр. P4₂/mnm). Значення факторiв недостовiрностi
RB становлять 0,060–0,069. Проаналiзовано особливостi ШПС Sr₂LnInTiO₇ та встановленi взаємозв’язки склад — будова ШПС. Определена протяженность области соединений со слоистой перовскитоподобной структурой (СПС) в ряду двухслойных перовскитов Sr₂LnInTiO₇. Синтезированы новые индотитанаты Sr₂LnInTiO₇ (Ln — La, Pr, Nd, Sm) при термообработке эквимолярных смесей
Sr₂TO₄ +LnInO₃ и определена их кристаллическая СПС методом рентгеновской дифракции на порошках. Установлена принадлежность СПС Sr₂LnInTiO₇ (Ln — La, Pr, Nd, Sm)
к структурному типу BaLa₂In₂O₇ (пр. гр. P4₂/mnm). Значения факторов недостоверности RB составляют 0,060–0,069. Проанализированы особенности СПС Sr₂LnInTiO₇ и установлены взаимосвязи состав–строение СПС. The extent of a region of compounds with layered perovskite-like structures (LPS) in the row of
two-layer perovskites Sr₂LnInTiO₇ is determined. The new indotitanates Sr₂LnInTiO₇ (Ln — La,
Pr, Nd, Sm) have been synthesized by heat treatment of equimolar mixtures Sr₂TO₄ +LnInO₃, and
their crystal LPS determined by X-ray powder diffraction. It is found that the LPS of Sr2LnInTiO7
(Ln — La, Pr, Nd, Sm) belongs to the BaLa₂In₂O₇ — type structure (sp. gr. P4₂/mnm). The final
RB values are equal to 0.060–0.069. The peculiarities of the two-layer LPS of Sr₂LnInTiO₇ are
analyzed, and the composition — constitution correlations of the LPS have been identified.